Inhibition of Glycogen Synthase Kinase 3β Increases the Proportion and Suppressive Function of CD19+CD24hiCD27+ Breg Cells - Li, Jinyang; Gao, Ji; Zhou, Haoming; Zhou, Jinren; Deng, Zhenghua; Lu, Yunjie; Rao, Jianhua; Ji, Guwei; Gu, Jian; Yang, Xinxiang; Xia, Yongxiang; Wang, Xuehao (Frontiers in Immunology, 2020)
CD19+CD24hiCD27+ memory Breg cells exhibit decreased abundance in patients with chronic graft-versus-host disease (cGVHD) after liver transplantation and produce less IL-10 than those from patients without cGVHD and healthy donors. Due to the lack of Breg cells and the difficulty in expanding them in vitro, in mouse models and early human clinical trials, the adoptive transfer of Breg cells to autoimmune diseases is greatly restricted. Glycogen synthase kinase 3β (GSK-3β) is a multifunctional serine/threonine (ser/thr) protein kinase that can participate in B cell growth, metabolic activity and proliferation. Phosphoprotein array analysis showed that p-GSK-3β-s9 was highly expressed in mBreg cells. Furthermore, here we demonstrated that GSK-3β expression in mBreg cells is lower than that observed in B cells by flow cytometry. We found that the treatment of B cells with the specific GSK-3β inhibitor SB216763 can significantly increase the proportion and immunosuppressive function of mBreg cells in vitro. Nuclear factor of activated T cells (NFAT) is one of a pivotal regulator of gene expression in adaptive immune system. Here we observed that inhibition of GSK-3β by SB216763 results in enhanced expression of NFATc1 in B cells, which is essential in regulating the ability of B cells to secrete il-10. By constructing a xGVHD mouse model, we observed that SB216763-treated mBreg cells effectively prevent xenogeneic GVHD. Here we propose a novel strategy using SB216763 to inhibit GSK-3β and then enhance the proportion and immunosuppressive function of mBreg cells by increasing the expression of NFATc1. This approach may be used as a therapy to ameliorate GVHD and inflammatory diseases.